2011
DOI: 10.1017/s0033291711002121
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of mRNA expression encoding chaperone and co-chaperone proteins of the glucocorticoid receptor in peripheral blood: association with depressive symptoms during pregnancy

Abstract: The presence of prenatal depressive symptoms appears to be associated with altered regulation of GR sensitivity. Peripheral expression of GR co-chaperone genes may serve as a biomarker for risk of developing depressive symptoms during pregnancy. The presence of such biomarkers, if confirmed, could be utilized in treatment planning for women with a psychiatric history.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 86 publications
4
34
0
2
Order By: Relevance
“…Our findings are consistent with the hypotheses of hormone sensitivity-mediated PPD risk put forth by Bloch et al, as well as previous work implicating an increased sensitivity of the stress system with antenatal depression (Katz et al, 2012).…”
supporting
confidence: 93%
“…Our findings are consistent with the hypotheses of hormone sensitivity-mediated PPD risk put forth by Bloch et al, as well as previous work implicating an increased sensitivity of the stress system with antenatal depression (Katz et al, 2012).…”
supporting
confidence: 93%
“…Indeed, there is evidence that normal pregnancy is associated with glucocorticoid resistance, as indicated by studies showing impaired GR-mediated negative-feedback regulation of the HPA axis [18], and reduced GR function [19]. Consistent with this, both the HPA axis and the inflammatory system are hyperactive during normal pregnancy.…”
Section: Clinical Relevance Of Antenatal Depressionmentioning
confidence: 82%
“…Consistent with this, both the HPA axis and the inflammatory system are hyperactive during normal pregnancy. More importantly, there is also specific evidence that GR resistance is more marked in women who experience depressive symptoms or stress during pregnancy, as shown by both a further reduction of GR function [19] and an even higher activity of the HPA axis and the inflammatory system [20,21]. We propose that these biological changes affect both mothers' and children's behaviour.…”
Section: Clinical Relevance Of Antenatal Depressionmentioning
confidence: 82%
“…Recently, it was shown that the minor allele is associated with decreased abundance of the predominant GRalpha receptor isoform in the dorsolateral prefrontal cortex, which results in abnormal GR expression (Sinclair et al, 2012). Katz et al (2012) found increased expression of NR3C1 and FKBP5 during pregnancy. In depressed women, the increase in FKBP5 expression was smaller than in non-depressed women.…”
Section: Discussionmentioning
confidence: 99%